Corporate financial distress of industry level listings in Vietnam - Duc Hong Vo; Binh Ninh Vo Pham; Chi Minh Ho; Michael McAleer (Journal of Risk and Financial Management, 2019)
Any critical analysis of the corporate financial distress of listed firms in international exchange would be incomplete without a serious dissection at the industry level, because of the different levels of risks concerned. This paper considers the financial distress of listed firms at the industry level in Vietnam over the last decade. Two periods are considered, namely during the Global Financial Crisis (GFC) (2007-2009) and post-GFC (2010-2017). The logit regression technique is used to estimate alternative models based on accounting and market factors. The paper also extends the analysis to include selected macroeconomic factors that are expected to affect the corporate financial distress of listed firms at the industry level in Vietnam. The empirical findings confirm that the corporate financial distress prediction model, which includes accounting factors with macroeconomic indicators, performs much better than alternative models. In addition, the evidence confirms that the GFC had a damaging impact on each sector, with the Health & Education sector demonstrating the most impressive recovery post-GFC, and the Utilities sector recording a dramatic increase in bankruptcies post-GFC.
Keywords: 330; Vietnam; bankruptcy; corporate financial distress; distance to default; fundamentals; Global Financial Crisis; industry level; listed firms